Gender inequalities in health and health care services use in Catalonia (Spain) - Fernandez, E. (BMJ Group, 1999)
BACKGROUND AND OBJECTIVES: While socio-economically derived differences in health and health services use have long been a subject of study, differences based on gender, considered as the explicative variable, have scarcely been quantified from population-based data. The aim of this investigation was to analyse inequalities in health and health care services utilisation between men and women in Catalonia (Spain). DESIGN, SETTING, PARTICIPANTS, AND MEASURES: Data from the Catalan Health Interview Survey, a cross sectional survey conducted in 1994, were used. A total of 6604 women and 5641 men aged 15 years or over were included for analysis. Health related variables studied were self perceived health, restriction of activity (past two weeks), and presence of chronic conditions; health services use variables analysed were having visited a health professional (past two weeks), an optometrist (12 months), or a dentist (12 months); and hospitalisation (past 12 months). Age standardised proportions were computed according to gender, and prevalence odds ratios (OR) were derived from logistic regression equations. MAIN RESULTS: Women more frequently rated their health as fair or poor than men (29.8% v 21.4%; OR = 1.22; 95% CI: 1.10, 1.34). More women than men reported having restricted activity days (OR = 1.86; 95% CI: 1.59, 2.18) and chronic conditions (OR = 1.74; 95% CI: 1.60, 1.89). The proportion of women visiting a health professional was slightly greater than that for men (OR = 1.20; 95% CI: 1.09, 1.31), as was the proportion of women visiting an optometrist (OR = 1.21; 95% CI: 1.11, 1.33), and a dentist (OR = 1.43; 95% CI: 1.31, 1.55). The proportion of hospitalisation was lower in women (6.6%) than in men (7.7%; OR = 0.73; 95% CI: 0.63, 0.85). When health services use was analysed according to self perceived health, women declaring good health reported a greater probability of consulting a health professional (OR = 1.35; 95% CI: 1.20, 1.52). There were no differences in respect to hospitalisation, visits to the optometrist and to the dentist. CONCLUSIONS: These results indicate a pattern close to the inverse care law, as women, who express a lower level of health and thus would need more health care, are not, however, using health services more frequently than men.